Improved Production of Majority Cellulases in Trichoderma reesei by Integration of cbh1 Gene From Chaetomium thermophilum - Jiang, Xianzhang; Du, Jiawen; He, Ruonan; Zhang, Zhengying; Qi, Feng; Huang, Jianzhong; Qin, Lina (Frontiers in Microbiology, 2020)
Lignocellulose is an abundant waste resource and has been considered as a promising material for production of biofuels or other valuable bio-products. Currently, one of the major bottlenecks in the economic utilization of lignocellulosic materials is the cost-efficiency of converting lignocellulose into soluble sugars for fermentation. One way to address this problem is to seek superior lignocellulose degradation enzymes or further improve current production yields of lignocellulases. In the present study, the lignocellulose degradation capacity of a thermophilic fungus Chaetomium thermophilum was firstly evaluated and compared to that of the biotechnological workhorse Trichoderma reesei. The data demonstrated that compared to T. reesei, C. thermophilum displayed substantially higher cellulose-utilizing efficiency with relatively lower production of cellulases, indicating that better cellulases might exist in C. thermophilum. Comparison of the protein secretome between C. thermophilum and T. reesei showed that the secreted protein categories were quite different in these two species. In addition, to prove that cellulases in C. thermophilum had better enzymatic properties, the major cellulase cellobiohydrolase I (CBH1) from C. thermophilum and T. reesei were firstly characterized, respectively. The data showed that the specific activity of C. thermophilum CBH1 was about 4.5 folds higher than T. reesei CBH1 in a wide range of temperatures and pH. To explore whether increasing CBH1 activity in T. reesei could contribute to improving the overall cellulose-utilizing efficiency of T. reesei, T. reesei cbh1 gene was replaced with C. thermophilum cbh1 gene by integration of C. thermophilum cbh1 gene into T. reesei cbh1 gene locus. The data surprisingly showed that this gene replacement not only increased the cellobiohydrolase activities by around 4.1 folds, but also resulted in stronger induction of other cellulases genes, which caused the filter paper activities, Azo-CMC activities and β-glucosidase activities increased by about 2.2, 1.9, and 2.3 folds, respectively. The study here not only provided new resources of superior cellulases genes and new strategy to improve the cellulase production in T. reesei, but also contribute to opening the path for fundamental research on C. thermophilum.